A Estética Queer-Contracultural no romance Onde Andará Dulce Veiga? - Wizniewsky Amaral, João Pedro (Confluenze. Rivista di Studi Iberoamericani, 2018)
Onde Andará Dulce Veiga? is a novel in which contracultural elements and Queer Theory themes are part of its narrative. Thus, the hypothesis of this reading is that the countercultural aesthetics deconstructs the binary and heteronormative way of thinking genre. The most evident relation between Queer Theory and counterculture is perceived in the characters representation, as the narrator-protagonist, Márcia Felácio and Jacyr(a). Furthermore, the AIDS, a disease once related to the LGBT and countercultural movements, pervades the whole narrative denouncing a social problem.